The effect of different cooking methods on sensory attributes, physicochemical properties, and microbial safety of ostrich meat (Struthio camelus) (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The present work aimed to determine the impact of various cooking methods on sensory attributes, microbial safety, and physicochemical characteristics of ostrich meat to specify the best cooking method that guarantees the microbial safety of the meat as well as maintains nutritional values and is highly attractive to consumers. Materials and Methods: One hundred fresh leg muscles of ostriches were divided into five groups. Different cooking techniques were used for each group, as follows: roasting, boiling, grilling, frying, and microwaving. Each method was examined by evaluating the impact of various cooking methods on sensory attributes, proximate chemical analysis, protein and fat oxidation parameters, microbial load, changes in color, and the shear force of ostrich meat. Results: The oven-roasting and grilling methods are highly recommended and more appealing to consumers since they produce tenderer and juicier meat, cause less cooking loss (CL), and maintain the nutritive value of ostrich meat; however, they have the highest protein and fat oxidation rates. On the other hand, boiling and frying methods revealed good fat oxidation parameters, the highest CL, and preserved nutritional value, but unfortunately, they were not highly preferred by consumers. From a hygienic point of view, grilling and microwave cooking are the methods that ensure the microbiological safety of cooked ostrich meat, as they significantly reduce Enterobacteriaceae and psychrotrophic bacterial counts, among other cooking methods. Conclusion: The oven roasting and grilling methods were the most preferable thermal cooking techniques, as they achieved the highest acceptability to consumers and maintained the nutritive values of ostrich meat.Adv. Vet. Anim. Res., 11(1): 194-202, March 2024http://doi.org/10.5455/javar.2024.k765